The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1212655110
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the microRNA-183/96/182cluster results in syndromic retinal degeneration

Abstract: The microRNA-183/96/182 cluster is highly expressed in the retina and other sensory organs. To uncover its in vivo functions in the retina, we generated a knockout mouse model, designated "miR-183CGT/GT ," using a gene-trap embryonic stem cell clone. We provide evidence that inactivation of the cluster results in early-onset and progressive synaptic defects of the photoreceptors, leading to abnormalities of scotopic and photopic electroretinograms with decreased b-wave amplitude as the primary defect and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
241
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(260 citation statements)
references
References 109 publications
(117 reference statements)
14
241
4
1
Order By: Relevance
“…Previous studies have reported that the down-regulation of expression of the miR-183 cluster in different models can lead to retinal degeneration (4)(5)(6). Although the retinal degeneration observed in our DKO mice was similar to that reported in previous models, the defects in the cones were distinct from those observed in other studies.…”
Section: Discussionsupporting
(Expert classified)
See 1 more Smart Citation
“…Previous studies have reported that the down-regulation of expression of the miR-183 cluster in different models can lead to retinal degeneration (4)(5)(6). Although the retinal degeneration observed in our DKO mice was similar to that reported in previous models, the defects in the cones were distinct from those observed in other studies.…”
Section: Discussionsupporting
(Expert classified)
“…Wholesale and individual disruption of miRNAs has been shown to result in various retinal defects and other sensorial diseases (4)(5)(6). The retinal photoreceptor is a type of ciliated neuron in which the miR-183 cluster represents the most highly expressed miRNAs.…”
mentioning
confidence: 99%
“…This is also the first example to our knowledge of a microRNA mutation with a causative role in inherited retinal dystrophies in patients, as to date, microRNAs have been linked to such diseases only in mouse (45).…”
Section: Discussionmentioning
confidence: 99%
“…miR-96 was found to be overexpressed in many types of cancer and to promote cancer cell proliferation, metastasis, and metabolism (Guo et al, 2014;Yu et al, 2014;Zhang et al, 2014). In addition, miR-96, together with miR-182 and miR-183, are highly expressed in the retina and are associated with syndromic retinal degeneration (Lumayag et al, 2013). Moreover, a mutation in the seed region of miR-96 can result in progressive hearing loss (Lewis et al, 2009;Mencia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%